China promotes coastal wetland restoration to protect wetland ecosystems - Quansheng Wang; Guoqing Han; Qi Zhang (Environmental Sciences Europe)
Abstract In 2023, China amended the Marine Environmental Protection Law, making it clear that China needs to make greater efforts to protect the marine ecological environment, including the coastal wetland environment. The concept of land and sea integration integrates the management of coastal wetland ecosystems with the management of marine ecosystems to promote the improvement of China’s marine and coastal wetland ecosystems. Coastal wetlands are the interconnected transition zones between terrestrial and marine ecosystems, playing a crucial role in the overall ecosystem. China has rich coastal wetland resources, distributed in 11 provinces and cities along the eastern coast of China. During the economic development of the past 70 years, the area of coastal wetlands has significantly decreased, leading to damage to coastal wetland resources. Although China began to focus on restoring and maintaining wetlands after the 1970s, it still faces various risks and challenges, including reclamation, urban expansion, and pollution. In the future, China will need to enhance the classification and grading standards of coastal wetlands, establish general guidelines for ecological restoration, improve the regulatory system in ecological restoration, and strengthen the monitoring mechanisms of coastal wetlands to restore and maintain coastal wetland resources. This paper finds that China has taken steps to restore coastal wetlands. Although these steps have had a relatively significant impact, the rate of coastal wetland destruction continues to exceed the rate of restoration. To address this imbalance, China needs a comprehensive approach to increased support in terms of systems, technology, and financial investment. This will help increase the restoration efforts and improve the ecological quality of China’s coastal wetlands.